2008
DOI: 10.1002/humu.20754
|View full text |Cite
|
Sign up to set email alerts
|

Mutations and polymorphisms of the gene of the major human blood protein, serum albumin

Abstract: Communicated by Jürgen HorstWe have tabulated the 77 currently known mutations of the familiar human blood protein, serum albumin (ALB). A total of 65 mutations result in bisalbuminemia. Physiological and structural effects of these mutations are included where observed. Most of the changes are benign. The majority of them were detected upon clinical electrophoretic studies, as a result of a point mutation of a charged amino acid residue. Three were discovered by their strong binding of thyroxine or triiodothy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(79 citation statements)
references
References 93 publications
1
72
0
2
Order By: Relevance
“…At least 77 mutations have been identified in the albumin gene [24]. In addition, there are 43 registered cases of analbuminemia that leads to low blood pressure, edema, fatigue, hypercholesterolemia and lipodystrophy (http://www.albumin.org/).…”
Section: Heterogeneity Of Albumin and Its Thiol Redox Statusmentioning
confidence: 99%
“…At least 77 mutations have been identified in the albumin gene [24]. In addition, there are 43 registered cases of analbuminemia that leads to low blood pressure, edema, fatigue, hypercholesterolemia and lipodystrophy (http://www.albumin.org/).…”
Section: Heterogeneity Of Albumin and Its Thiol Redox Statusmentioning
confidence: 99%
“…SA was named a century and half ago (Denis, 1859) and deeply investigated over the last century (Peters, 1996). In 1932, HSA was separated from plasma proteins (Race, 1932); in 1934, HSA was crystallized (Hewitt, 1936); in 1939, the neutral-to-acid (i.e., N-to-F) conformational transition was detected (Luetscher, 1947); in 1940, HSA was purified for intravenous use as a blood substitute (Cohn, 1941); in 1954, the first two cases of analbuminemia were reported (Bennhold et al, 1954); in 1960, the HSA ''domain'' structure was proposed (Foster, 1960); in 1975, the primary structure of HSA was deduced (Meloun et al, 1975), and the characterization of specific drug binding sites started (Sudlow et al, 1975); in 1979, the HSA gene was isolated (Sargent et al, 1979); in 1981, the nucleotide sequence of HSA cDNA was reported (Lawn et al, 1981); in 1986, the complete gene sequence of HSA was determined (Minghetti et al, 1986), and the expression, the cleavage, and the secretion of HSA from cultured yeast Saccharomyces cerevisiae was reported (Hinchcliffe and Kenney, 1986); starting from 1989, many HSA mutations were localized (Peters, 1996;Minchiotti et al, 2008;Otagiri and Chuang, 2009); in 1992, the ''heart-shaped'' three-dimensional structure of HSA was determined (He and Carter, 1992); in 1995, the ferrous tetraphenylporphirinatoiron (FeP(II)) was incorporated in HSA to obtain a red blood cell substitute (Komatsu et al, 1995); in 1999, the role of HSA in heme-Fe scavenging was highlighted (Miller and Shaklai, 1999), and human serum heme-albumin (HSA-heme) was engineered to become a O 2 carrier (Carter et al, 1999;Komatsu et al, 2004a); and starting from 2001, the detoxifying role of HSA-heme-Fe towards reactive nitrogen species (RNS) and reactive oxygen species (ROS) was underlined (Monzani et al, 2001;Ascenzi et al, 2009a).…”
Section: Introductionmentioning
confidence: 98%
“…There have been very few studies that have attempted to study FFA binding to genetic variants of HSA. Although a few noted increased FFA binding (Minchiotti et al, 2008), majority of the mutations had none or less effect, especially those on the surface of the protein (Otagiri and Chuang, 2009). Therefore, while the existence of other genetic HSA variants in the populace remains to be screened or unknown, our study presents a possible mechanism on what alterations on HSA has on FFA binding since we carried out amino acid substitutions in key FFAbinding pockets of HSA.…”
Section: Discussionmentioning
confidence: 78%